Correlation between Cardiorespiratory Fitness and Fatigue Severity Scale (FSS) on Systemic Lupus Erythematosus (SLE) Patients at RSUP Dr. Hasan Sadikin Bandung - Thea Yovita; Sumartini Dewi; Sunaryo Barki Sastradimaja (Indonesian Rheumatology Association, 2019)
Background Systemic Lupus Erythematosus (SLE) is a multifactorial and heterogenous systemic autoimmune disease, involving multisystem organ and marked with the production of autoantibodies. SLE has general constitutional sympton such as fatigue and usually is the main symptom causing limited functional condition on patients. Assessment for cardiorespiratory fitness can be done with various methods, one of them measuring Metabolic Equivalents (METs). The purpose of this study was to examine the correlation between cardiorespiratory fitness and Fatigue Severity Scale (FSS). Method The sampling method used was the total sampling method. Out-patients diagnosed with SLE were screened via medical records according to inclusion and exclusion criteria. SLE patients filled an Indonesian version of the FSS questionnaire sheet and did the six-minute walk test based on standard protocol on a 30-meter track. The total distance patients had crossed was turned into VO2 max with Nury equation, then turned again into cardiorespiratory fitness with METs unit. A correlation analysis between cardiorespiratory fitness and FSS was done next. Results There were 28 patients participating in this research. Correlation analysis resulted in a negative correlation with no statistical meaning between cardiorespiratory fitness and FSS (r = -0,27; p > 0,05). Conclusion There is no correlation between cardiorespiratory fitness and FSS in SLE patients. Keywords Correlation, Cardiorespiratory Fitness, Fatigue Severity Scale, Systemic Lupus Erythematosus